Metals, semimetals and semiconductors for spinelectronics - Stamenov, Plamen (Trinity College (Dublin, Ireland). School of Physics, 2008)
The development of the new field of spin electronics depends upon the existence of materials and structures that may be used as effective spin-polarised current injectors, transmitters, manipulators and detectors. Potential high-efficiency injection structures include tunnel, Schottky, hetero and p-n junctions, barriers employing ferromagnetic metals (ideally half-metals) and magnetic or semimagnetic semiconductors. As media with long carrier mean free path and spin- coherence length, an eventual transmitter, few possibilities are currently explored. These are classical IV, III-V, II-VI semiconductors, and semimetals such as bismuth and graphite. Various means are used to manipulate and detect spin-polarised currents -optical (optical pumping, magnetic circular dichroism and Kerr effect), electrostatic (FET with spin-orbit coupling) and galvanic (different types of Hall effect and magnetoresistive devices). The experiments described in this thesis are devised to explore the first two bits in the above ‘spin chain’. They include the possibility to use Schottky barriers as efficient spin- injectors, including the more fundamental aspect of spin-polarisation measurement employing Schottky barriers; the modelling of the electronic transport through tunnel junctions with high magnetoresistive ratios; the possibilities for direct magnetic detection of spin polarisation injected through metal-metal junctions; the fundamental transport and magnetisation properties of graphite (a good example of a semi-metal) and the magnetic properties of multi-walled carbon nanotubes; and the magneto-transport through Co:ZnO (a candidate for room temperature semimagnetic semiconductor).
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin